Technology and equipment modernization of rolling process on wide-strip mill of the first generation - Шепель, Анна Александровна (Technology audit and production reserves, 2014)
The existing technologies of hot strip production in the mills of different generations are considered in the article on the basis of literary analysis, the major disadvantages are identified and development trends of wide-strip hot mills are determined. The outmoded and physically worn-out equipment is used in continuous wide-strip mills 1700 of Illich Iron and Steel Works in of Mariupol. To prolong the life of the equipment and the maintenance of competitiveness requires the equipment reconstruction and improving the technology of hot rolling of wide strips. The practical recommendations to improve the technology and mechanical equipment for the production of hot-rolled wide strips in condition of WSHM 1700 of Illich Iron and Steel Works in of Mariupol are proposed in the article. The proposed solutions will address the following actual tasks: the expansion of the product assortment, improving its quality with resource-saving and material-saving and, consequently, effectiveness increase of specific industrial enterprises.